Output feedback robust control for teleoperated manipulator robots with different workspace. (15th November 2022) - Sanchez, Misael; Cruz-Ortiz, David; Ballesteros, Mariana; Salgado, Ivan; Chairez, Isaac
Abstract: This article solves the tracking trajectory problem of teleoperated robotic systems with different workspaces. The overall robotic system satisfies a regular master–slave structure with a delta-robot as the master device and a planar manipulator attached to a Cartesian robot with five degrees of freedom (DOFs) as the slave device. A forward kinematics analysis describes the workspace for the delta-robot and the five-DOFs manipulator. A coordinate transformation based on sigmoidal functions establishes the relation between the workspaces for both robotic devices. The obtained transformation yields a feasible workspace for the slave robot. Then, an inverse kinematics analysis provides the desired reference trajectories. The tracking trajectory control implements a robust strategy based on Barrier Lyapunov functions. The barrier controller does not allow the slave robot to reach non-attainable configurations. State-dependent gains characterized the obtained controller taking into account the different workspaces for each device. Numerical results describe the suggested controller applied in a virtual teleoperated robot and a real robotic system platform. The obtained results confirm the improvements (measured in terms of the mean square error and the l 2 norm of the applied controls) of the proposed controller against a traditional state feedback realization. Furthermore, the results show that the trajectories of the slave robot do not leave the valid workspace. Highlights: Output feedback control for teleoperated manipulators under state constraints. Adaptive control formulation based on logarithmic barrier Lyapunov functions. Super-twisting differentiator implementation to obtain the tracking error derivative. Experimental evaluations on a manipulator (slave) and a Delta robot (master).